2014-2016 ‫أﺳﺎﻟﻴﺐ‬‫إدارة‬ ‫اﻟﻤخاﻃﺮ‬ ‫اﻟﻤﺎﻟﻴﺔ‬ ‫ﻓﻲ‬ ‫ﺷﺮﻛﺎت‬ ‫اﻟﺘﺄﻣﻴﻦ‬ ‫وﻣﺘﻄﻠﺒﺎت‬ ‫ﺗﻔﻌﻴﻠﻬﺎ‬ ‫دراﺳﺔ‬ ‫ﺣﺎﻟﺔ‬ ‫اﻟﺸﺮﻛﺔ‬ ‫اﻟﺠﺰاﺋﺮﻳﺔ‬‫ﻟﻠﺘﺄﻣﻴﻨﺎت‬ ‫و‬ ‫اﻟﻤﻔﺘﺸﻴﺔ‬ ‫اﻟﺠﻬﻮﻳﺔ‬ ‫ﻋﻨﺎﺑﺔ‬ ‫ﺧﻼل‬ ‫اﻟﻔﺘﺮة‬ ‫‪ - ‬ ‫أﻣﺎل‫ ﺑﻦ‬‫ﺳﺎﻟﻢ ‬; ‬‫ﻧﺪى‫ ﺟﻮاﻣﻊ‬ (My University, 2018)
Insurance Companies, are one of the most important financial non- banking, and in order to ensure continuty on survival and to be able to face the risk that are the subject of its activity and dealing with it, and to also be able to manage thier financial risk and to fulfill their obligations and to improve the financial status it must be the management of the varions component and find the methods to predict and court control of the financial risks before they occur and to preserve the financial status and good solvancy and to protect the intereste of the creditors. This may to the financial analysis methode, wich is considered and important means to guide analysts and managers for decisions of the crisis based on the measured to asseus the size of the risk, in addition to the indicators of the Early system ofen to see what’s new giving advance alerte the company if there is a risk of precautionary measures to take, and to create clear to activate all the ingredients of the foundations of govermance over right as a necessity to achieve the requirements for the management of financial risk in a dynamic envirenement wich may the eaten the contivity of the company and their survival in markets. ............................................................. تعتبر شركات التأمين من أهم الشركات المالية غير المصرفية، وذلك لضمان استمراريتها على قيد الحياة وأن تكون قادرة على مواجهة المخاطر التي موضوع نشاطها والتعامل معها، وأن تكون قادرة أيضاً على إدارتها المخاطر المالية والوفاء بالتزاماتهم ولتحسين الوضع المالي يجب إدارة الاختلافات المكون وإيجاد طرق التنبؤ بالمخاطر المالية والسيطرة عليها قبل حدوثها والحفاظ عليها الوضع المالي والملاءة الجيدة وحماية مصالح الدائنين. وقد يعود ذلك إلى أسلوب التحليل المالي الذي يعتبر وسيلة مهمة لتوجيه المحللين والمديرين قرارات الأزمة مبنية على قياس حجم المخاطر، بالإضافة إلى مؤشرات النظام المبكر في كثير من الأحيان لمعرفة ما هو جديد، قم بتنبيه الشركة مسبقًا إذا كان هناك خطر من الإجراءات الاحترازية التي يجب اتخاذها، وإنشاء واضح تفعيل كافة مقومات أسس الحكم على الحق كضرورة لتحقيق متطلباته إدارة المخاطر المالية في بيئة ديناميكية قد تؤثر على نشاط الشركة وأفرادها البقاء في الأسواق.